Desegregation and the Rhetorical Fight for African American Citizenship Rights : The Rhetorical/Legal Dynamics of "With All Deliberate Speed" - Paulson, Sally F., 1954- (Rhetoric, race, and religion., 2018)
"Focusing on the NAACP's twentieth-century attempt to overturn the 'separate but equal' doctrine through school desegregation cases. Desegregation and the Rhetorical Fight for African American Citizenship Rights analyzes the rhetorical/legal dynamics inherent in the struggle to determine African American citizenship rights. This book begins by identifying the fundamental dialectical tension existing within all American citizenship rights between the Declaration of Independence's guarantee of 'ideal equality' for all citizens as opposed to the Constitution's privileging of local, 'practical' decision-making through Article IV Sect. 2, the 'privileges and immunities' clause. It contends that, as a consequence of that dynamic, American citizenship rights are rhetorical concepts produced through arguments grounded in 'all the available means of persuasion,' including logical, emotional, and ethical appeals. Ultimately, this book demonstrates that the school desegregation issue comes down to a question of credibility/ethics. Recommended for scholars interested in communication, law, history, political science, and cultural studies"--Back cover.